Precipitation-hardening martensitic stainless steel for press plate, solid solution material thereof and aging treatment material
A tailored composition and two-phase structure in martensitic stainless steel enable high hardness and flatness in press plates by optimizing element ratios and treatment processes, addressing the challenges of shape modification and strength in precipitation-hardened martensitic stainless steel.
Patent Information
- Application Number
- JP2024176434
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2024-03-29
- Filing Date
- 2024-10-08
- Publication Date
- 2025-10-14
- Estimated Expiration
- 2044-10-08
AI Technical Summary
Precipitation-hardened martensitic stainless steel used for press plates faces challenges in achieving high hardness and ensuring flatness due to the precipitation of the ε-Cu phase, which affects the shape modification and strength properties.
A specific composition of martensitic stainless steel with controlled amounts of elements such as C, Si, Mn, Ni, Cr, Mo, Cu, Al, N, Ti, Nb, and Co, along with a two-phase structure of martensite and retained austenite, allows for high hardness and excellent flatness by adjusting the MA and H values to facilitate shape correction and aging treatment.
The solution-treated material achieves a hardness of less than 380 HV for easy shape correction, while the aged material reaches 450 HV or more, ensuring high hardness and excellent flatness in the press plates.
Smart Images

Figure 2025155627000001_ABST
Abstract
Description
[Technical Field]
[0001] The present invention relates to a precipitation-hardened martensitic stainless steel capable of producing a press plate having high hardness and excellent flatness, and to a solution-treated material and an aged material thereof. [Background technology]
[0002] Precipitation-hardening martensitic stainless steel such as SUS630 is used for press plates used in press-forming laminates such as multilayer printed wiring boards. The addition of Cu causes the precipitation of the ε-Cu phase, making it possible to obtain high strength.
[0003] For example, in Patent Document 1, Ti and Si are added to the ε-Cu phase to form Ni 16 A precipitation-hardened martensitic stainless steel has been disclosed that maintains high strength and toughness by controlling the distribution of Ti6Si7-based intermetallic compound phase (G phase) within the crystal grains. The G phase, which precipitates by aging heat treatment, i.e., Ni 16 Since X in X6Si7 can be substituted not only with Ti but also with Fe, Mn, and Nb, we have clarified the composition by adjusting the amount of Nb in particular.
[0004] Patent Document 2 discloses a method for manufacturing a press plate and the steel material thereof, in which austenitic stainless steel with a high austenite ratio containing 1.0 to 4.0 mass% Si is subjected to the necessary shape modification and then aging treatment to increase the surface hardness to 430 HV or more by strain aging. This document points out that it is difficult to sufficiently flatten a steel plate made of hard stainless steel with a surface hardness of 400 HV or more simply by shape modification using temper rolling or a tension leveler, and that if martensitic stainless steel is used, flatness cannot be ensured in the quenching or tempering process, and suggests that an austenitic stainless steel with little martensite and a high austenite ratio should be used. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent Publication No. 2021-134395 [Patent Document 2] Japanese Patent Application Laid-Open No. 2008-297601 Summary of the Invention [Problem to be solved by the invention]
[0006] Incidentally, precipitation-hardened martensitic stainless steel such as SUS630 is subjected to solution treatment at 1000°C or higher, followed by aging treatment at a temperature of around 500°C to achieve a predetermined hardness (strength). In other words, precipitation-hardened martensitic stainless steel for press plates must have a hardness that allows shape modification after solution treatment, while also being able to increase its strength to a sufficient hardness through subsequent aging treatment.
[0007] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a precipitation hardened martensitic stainless steel, a solution-treated material thereof, and an aged material thereof, which are capable of providing a press plate having high hardness and excellent flatness. [Means for solving the problem]
[0008] The precipitation hardening martensitic stainless steel for press plates of the present invention has a composition, in mass%, of C: 0.01 to 0.07%, Si: 0.05 to 2.25%, Mn: 0.5 to 5.0%, Ni: 4.5 to 10.0%, Cr: 10.0 to 17.0%, Mo: 0.1 to 1.50%, Cu: 0.30 to 5.0%, Al: 0.001 to 0.100%, N: 0.001 to 0.020%, Ti: 0.15 to 0.55%, Nb: 0.15 to 0.45%, Co: 0.03 to 0.80%, P: 0.04% or less, S: 0.0020% or less, with the balance being Fe and unavoidable impurities, wherein the composition is such that, when the mass% of element M is [M], MA=[Ni]+0.65×[Mn]+0.23×[Si]+0.62×[Cr]+0.25×[Mo]+0.35×[Cu]+30.6×([C]+[N])-16.5 The MA defined as is in the range of 1.0 to 4.5, and H=[Cu]+0.6×[Ni]+1.8×[Si]+3.8×[Ti]+1.8×[Nb]-0.9×[Mn]-13.8×([C]+[N]) The present invention is characterized in that H defined by the following formula is set to be in the range of 5.0 or more.
[0009] According to these characteristics, a press plate having high hardness and excellent flatness can be obtained through solution treatment and aging treatment.
[0010] Further, a solution-treated material of a precipitation-hardened martensitic stainless steel for press plates according to the present invention has a composition, in mass %, of C: 0.01 to 0.07%, Si: 0.05 to 2.25%, Mn: 0.5 to 5.0%, Ni: 4.5 to 10.0%, Cr: 10.0 to 17.0%, Mo: 0.1 to 1.50%, Cu: 0.30 to 5.0%, Al: 0.001 to 0.100%, N: 0.001 to 0.020%, Ti: 0.15 to 0.55%, Nb: 0.15 to 0.45%, Co: 0.03 to 0.80%, P: 0.04% or less, S: 0.0020% or less, with the balance being Fe and unavoidable impurities, wherein the composition is such that, when the mass % of element M is [M], H=[Cu]+0.6×[Ni]+1.8×[Si]+3.8×[Ti]+1.8×[Nb]-0.9×[Mn]-13.8×([C]+[N]) The steel sheet is characterized in that H, defined as above, is in the range of 5.0 or more, the steel sheet has a two-phase structure of martensite phase and retained austenite phase, the amount of the retained austenite phase is 0.2 to 8 volume %, and the steel sheet has a hardness of less than 380 HV.
[0011] According to this feature, it is possible to easily correct the shape, and also to impart high hardness through aging treatment, thereby making it possible to provide a press plate that has high hardness and excellent flatness.
[0012] In the above invention, the component composition is as follows, when the mass % of element M is [M]: MA=[Ni]+0.65×[Mn]+0.23×[Si]+0.62×[Cr]+0.25×[Mo]+0.35×[Cu]+30.6×([C]+[N])-16.5 The MA defined by the following formula may be in the range of 1.0 to 4.5. According to this feature, shape correction is facilitated, and high hardness is imparted through aging treatment, making it possible to provide a press plate that has high hardness and excellent flatness.
[0013] Further, an aged material of precipitation hardening martensitic stainless steel for press plates according to the present invention has a composition, in mass%, of C: 0.01 to 0.07%, Si: 0.05 to 2.25%, Mn: 0.5 to 5.0%, Ni: 4.5 to 10.0%, Cr: 10.0 to 17.0%, Mo: 0.1 to 1.50%, Cu: 0.30 to 5.0%, Al: 0.001 to 0.100%, N: 0.001 to 0.020%, Ti: 0.15 to 0.55%, Nb: 0.15 to 0.45%, Co: 0.03 to 0.80%, P: 0.04% or less, S: 0.0020% or less, with the balance being Fe and unavoidable impurities, wherein the composition is such that, when the mass% of element M is [M], MA=[Ni]+0.65×[Mn]+0.23×[Si]+0.62×[Cr]+0.25×[Mo]+0.35×[Cu]+30.6×([C]+[N])-16.5 The MA defined by the above formula is in the range of 1.0 to 4.5, and the hardness is 450 HV or more.
[0014] According to this feature, it is possible to provide a press plate that has high hardness and excellent flatness.
[0015] The composition of the element M is expressed as follows, where [M] is the mass % of the element M: H=[Cu]+0.6×[Ni]+1.8×[Si]+3.8×[Ti]+1.8×[Nb]-0.9×[Mn]-13.8×([C]+[N]) According to this feature, it is possible to provide a press plate having high hardness and excellent flatness. [Brief explanation of the drawings]
[0016] [Figure 1] 1 is a table showing the chemical compositions of steels used in the test. [Figure 2] 1 is a table showing test results. DETAILED DESCRIPTION OF THE INVENTION
[0017] As described above, precipitation-hardened martensitic stainless steel for press plates is required to have a relatively low hardness after solution treatment, while being able to obtain sufficient hardness after aging. The inventors have conducted extensive research into the effect of adding Co together with Nb to martensitic stainless steels that achieve such hardness, and have found that by adjusting the steel composition so that an austenite phase remains after solution treatment, it is possible to obtain the desired hardness both after solution treatment and aging. The composition of such steel may be as follows:
[0018] That is, the precipitation hardening martensitic stainless steel for press plates according to this embodiment has a composition, in mass%, of C: 0.01 to 0.07%, Si: 0.05 to 2.25%, Mn: 0.5 to 5.0%, Ni: 4.5 to 10.0%, Cr: 10.0 to 17.0%, Mo: 0.1 to 1.50%, Cu: 0.30 to 5.0%, Al: 0.001 to 0.100%, N: 0.001 to 0.020%, Ti: 0.15 to 0.55%, Nb: 0.15 to 0.45%, Co: 0.03 to 0.80%, P: 0.04% or less, and S: 0.0020% or less, with Co being included in addition to Nb.
[0019] Furthermore, the composition of the element M is expressed as follows, where [M] is the mass% of the element M: MA=[Ni]+0.65×[Mn]+0.23×[Si]+0.62×[Cr] +0.25×[Mo]+0.35×[Cu] +30.6×([C]+[N])-16.5 The MA defined as follows is in the range of 1.0 to 4.5, H=[Cu]+0.6×[Ni]+1,8×[Si]+3.8×[Ti] +1.8×[Nb]-0.9×[Mn]-13.8×([C]+[N]) H defined as above is set to be in the range of 5.0 or more.
[0020] Here, it has been found that a composition containing only a small amount of Co along with the above-mentioned Nb can achieve a sufficiently large difference in hardness before and after aging treatment, and can stabilize the hardness before aging treatment, i.e., after solution treatment, to a hardness that allows for shape correction. Although Co is an austenite phase stabilizer, the above-mentioned MA value serves as an indicator of the stabilization of the austenite phase with this small amount of Co. By setting the MA value within the above range, the amount of retained austenite (residual γ phase) after solution treatment can be maintained at an appropriate level, resulting in a relatively low hardness after solution treatment, and excellent flatness can be achieved by shape correction of the sheet material. Incidentally, Co is contained in a relatively higher amount in the ε-Cu phase than in the G phase, which affects the precipitation morphology of the compounds. The above-mentioned H value is an indicator of the hardness obtained after aging treatment, and the range of the H value is determined taking into account the precipitation morphology of the compounds with the addition of this small amount of Co. By setting the H value within the above range, it is possible to achieve sufficient hardness by aging treatment, rather than a hardness that allows for shape correction. In other words, by adding only a small amount of Co, the mechanical strength of the base material consisting of the martensite phase is increased, and the mechanical strength of the aged material can be maintained at a high level despite the presence of the austenite phase.
[0021] The material after solution treatment is required to have a two-phase structure of martensite phase + retained austenite phase, with the amount of retained austenite phase being 0.2 to 8% by volume, and a hardness of less than 380 HV. To obtain such a solution treated material, the MA value is in the above-mentioned range of 1.0 to 4.5, preferably in the range of 1.2 to 3.5, and more preferably in the range of 1.4 to 2.5.
[0022] Furthermore, an aged material is required to have a hardness of 450 HV or more. To obtain such an aged material, the value of H is in the above-mentioned range of 5.0 or more, preferably in the range of 6.0 to 15.0, and more preferably in the range of 7.0 to 12.0. The upper limit of the value of H is preferably set so as to prevent embrittlement of the steel material during manufacturing.
[0023] The press plate in this example can be manufactured as follows. First, steel having the above-described chemical composition is cast, hot-rolled, and then cold-rolled to obtain a strip steel material of a predetermined thickness. The obtained strip steel material is subjected to a solution treatment, and upon cooling, martensite transformation occurs while leaving a portion of the austenite phase remaining. The solution treatment involves holding the material at a predetermined temperature within a range of, for example, 1000 to 1150°C, followed by water cooling. This allows for the production of a solution-treated material of precipitation-hardened martensitic stainless steel for press plates.
[0024] Next, the strip steel material that has become a solid solution treated material is subjected to shape correction. For example, a tension leveler can be suitably used for shape correction. By setting the hardness of the solid solution treated material to less than 380 HV as described above, the burden of shape correction on the manufacturing process can be relatively reduced. For example, excellent flatness can be obtained by simply performing shape correction using a tension leveler.
[0025] Finally, the steel plate is aged to obtain a predetermined hardness. The aging treatment can be performed, for example, by holding the plate at 400 to 600°C for 30 minutes to 10 hours. This allows the hardness after aging to be 450 HV or more as described above. This allows an aged precipitation-hardened martensitic stainless steel for press plates to be obtained.
[0026] In this manner, a press plate having high hardness and excellent flatness can be obtained.
[0027] [Testing of solution treated and aged materials] Next, the results of tests on hardness and other properties of plates made from a plurality of precipitation hardened martensitic stainless steels will be described.
[0028] For steels having the chemical compositions shown in Examples 1 to 11 and Comparative Examples 1 to 8 in Figure 1, 20 kg steel ingots were cast, hot forged to obtain forged plates, and then cold rolled to obtain steel plates with a thickness of 1.6 mm. The obtained steel plates were solution treated by holding at 1050°C for 2.5 minutes and cooled to obtain solution-treated materials. Furthermore, a portion of the solution-treated materials was subjected to shape correction and aging treatment to obtain aged materials.
[0029] As shown in Figure 2, the Vickers hardness (solution hardness) of the resulting solution-treated materials was measured, and the amount of residual γ phase was also measured. The amount of residual γ phase was measured by EBSD (electron backscatter diffraction) using a field emission scanning electron microscope (FE-SEM; JEOL Ltd. JSM-7001F). The flatness of the solution-treated materials after shape correction was also measured. Flatness was determined by placing a 2-m ruler on top of the steel plate placed on a surface plate and measuring the maximum distance between the top surface of the steel plate and the bottom surface of the ruler. A distance of 1 mm or less was evaluated as "excellent" and marked with a "◎." Similarly, a distance of more than 1 mm but less than 3 mm was evaluated as "good" and marked with a "◯." A distance of more than 3 mm but less than 5 mm was evaluated as "passable" and marked with a "△." A distance of more than 5 mm was evaluated as "fail" and marked with an "X." Furthermore, the Vickers hardness (aging hardness) of the aged materials was also measured.
[0030] As shown in the figure, for the steels of Examples 1 to 11, the flatness of the solution-treated materials after shape correction was all "fair" or better, and the hardness of the aged materials was 450 HV or higher. The above-mentioned MA values were in the range of 1.0 to 4.5, the H values were in the range of 5.0 or higher, the residual γ content of the solution-treated materials was in the range of 0.2 to 8.0 volume %, and the hardness was 380 HV or less except for Example 1. In Example 1, the hardness of the solution-treated material was set to a relatively high 386 HV, but the flatness was only "fair."
[0031] On the other hand, in Comparative Example 1, the Mn content was lower than in the Examples, and the MA value was low. Also, in Comparative Example 2, the Ni content was lower, and the MA value was low. In both cases, the amount of retained γ was low, and the flatness was "bad." It is thought that the low amount of retained γ made the solution-treated material relatively hard, and the flatness did not improve even after shape correction.
[0032] In Comparative Example 3, although the amounts of each element in the composition were comparable to those in the Examples, the MA value was large and the H value was small. As a result, the hardness of the aged material was low. It is believed that the increase in the MA value increased the amount of retained γ, which excessively reduced the hardness of the solution-treated material, and therefore the aged material did not achieve sufficient hardness. In addition, the decrease in the H value is believed to have reduced the precipitation hardening ability during aging, which is also believed to be one of the reasons why the aged material did not achieve sufficient hardness.
[0033] In Comparative Example 4, the amount of each element in the composition was similar to that of the Examples, but the value of H was small. As a result, the hardness of the aged material was low. This is thought to be because the solution-treated material had the same hardness as the Examples, but the value of H was small, and the precipitation hardening ability during aging was low.
[0034] In Comparative Example 5, the Si content was low. As a result, the hardness of the aged material was low. Although the hardness of the solution-treated material was equivalent to that of the Examples, it is believed that the low Si content prevented sufficient hardness from being obtained by aging treatment.
[0035] Comparative Example 6 contained almost no Co, but the contents of other components in the composition and the MA value were almost the same as those of Example 7. Comparative Example 6 also had almost the same solution hardness as Example 7, but the aging hardness was low. In other words, it was found that the Co content of Example 7 was an amount that had almost no effect on the solution hardness, but contributed greatly to the aging hardness. The same is true for the relationship between Comparative Example 7 and Example 11, and the relationship between Comparative Example 8 and Example 2.
[0036] Thus, with the steels of Examples 1 to 11, it is possible to impart high hardness to the aged material while imparting a relatively low hardness to the solution-treated material so that excellent flatness can be obtained by shape correction. In other words, it is possible to obtain precipitation-hardened martensitic stainless steels, and their solution-treated and aged materials, which can provide press plates having high hardness and excellent flatness.
[0037] The ranges of the chemical composition of the steels of the present invention, including Examples 1 to 11, are determined as follows.
[0038] C contributes to increasing mechanical strength through solid solution, while also stabilizing the austenite phase, suppressing the formation of δ-ferrite at high temperatures and increasing the amount of residual austenite after solution treatment. Therefore, excessive C content reduces the precipitation hardening ability during aging. Taking these factors into consideration, the C content is set within the range of 0.01 to 0.07%, preferably 0.02 to 0.06%, and more preferably 0.03 to 0.05%, by mass.
[0039] Si is added for deoxidation and is an important element for generating G phase by aging treatment to obtain mechanical strength. However, it is also a ferrite-forming element, and excessive content leads to an increase in the δ-ferrite phase, deteriorating hot workability. In consideration of these factors, the Si content is set within the range of 0.05 to 2.25%, preferably 1.05 to 2.05%, and more preferably 1.35 to 1.85%, by mass%.
[0040] Mn is an element that stabilizes the austenite phase, suppressing the formation of the δ-ferrite phase while contributing to the formation of retained austenite. On the other hand, excessive Mn content causes a large amount of austenite to remain, reducing the mechanical strength after aging treatment. Taking these factors into consideration, the Mn content is set within the range of 0.5 to 5.0%, preferably 0.6 to 4.0%, and more preferably 0.8 to 3.0%, by mass%.
[0041] Ni is an element that stabilizes the austenite phase, contributes to the formation of retained austenite while suppressing the formation of the δ-ferrite phase, and is an important element that contributes to the formation of the G phase by aging treatment and thereby contributes to an increase in mechanical strength. On the other hand, if it is contained in excess, a large amount of austenite phase will remain, reducing the mechanical strength after aging treatment. In consideration of these factors, the Ni content is set within the range of 4.5 to 10.0%, preferably 5.5 to 9.0%, and more preferably 6.5 to 8.0%, by mass%.
[0042] Cr is an element necessary for ensuring the corrosion resistance of stainless steel and also contributes to the formation of retained austenite. However, excessive Cr content can lead to the formation of δ-ferrite phase, resulting in a decrease in hot workability. Taking these factors into consideration, the Cr content is set within the range of 10.0 to 17.0%, preferably 12.0 to 16.0%, and more preferably 13.0 to 15.0%, by mass.
[0043] Mo is an element necessary for ensuring the corrosion resistance of stainless steel and also contributes to the formation of retained austenite. However, excessive Mo content leads to the formation of δ-ferrite phase, resulting in a decrease in hot workability. Taking these factors into consideration, the Mo content is set within the range of 0.1 to 1.50%, preferably 0.6 to 1.20%, and more preferably 0.7 to 1.00%, by mass.
[0044] Cu is an element that stabilizes the austenite phase, contributes to the formation of retained austenite while suppressing the formation of the δ-ferrite phase, and is an important element that generates the ε-Cu phase through aging treatment, thereby contributing to an increase in mechanical strength. On the other hand, if it is contained in excess, a large amount of austenite phase will remain, reducing the mechanical strength after aging treatment. In consideration of these factors, the Cu content is set within the range of 0.30 to 5.0%, preferably 0.40 to 3.0%, and more preferably 0.50 to 1.5%, by mass%.
[0045] Al is added for deoxidation and is an effective element for stably containing Nb and Ti, which are easily oxidized and therefore have low yields when added to the molten metal. However, since Al increases the martensitic transformation start temperature (Ms point), excessive addition inhibits the formation of retained austenite. It also increases the δ-ferrite phase, deteriorating hot workability. Taking these factors into consideration, the Al content is set within the range of 0.001 to 0.100%, preferably 0.002 to 0.060%, and more preferably 0.002 to 0.020%, by mass.
[0046] N is an element that stabilizes the austenite phase and contributes to the formation of retained austenite while suppressing the formation of the δ-ferrite phase. However, excessive N content results in a large amount of austenite remaining, reducing the mechanical strength after aging. It also forms nitrides, primarily with Ti, which can cause fracture initiation in press plates. Furthermore, it can change the Ms point and cause slab cracking. Taking these factors into consideration, the N content is set within the range of 0.001 to 0.020%, preferably 0.002 to 0.015%, and more preferably 0.003 to 0.010%, by mass.
[0047] Ti is an important element that generates a G phase during aging treatment and contributes to increasing mechanical strength. However, excessive Ti content can cause the formation of a δ ferrite phase, resulting in a decrease in hot workability. It can also change the Ms point, potentially causing slab cracking. Taking these factors into consideration, the Ti content is set within the range of 0.15 to 0.55%, preferably 0.20 to 0.50%, and more preferably 0.25 to 0.45%, by mass.
[0048] Nb is an important element that generates a G phase by aging treatment and contributes to increasing mechanical strength. However, excessive Nb content generates a δ ferrite phase, resulting in a decrease in hot workability. It may also change the Ms point and cause slab cracking. Taking these factors into consideration, the Nb content is set within the range of 0.15 to 0.45%, preferably 0.20 to 0.40%, and more preferably 0.25 to 0.35%, by mass%.
[0049] Co stabilizes the passive film, improving the corrosion resistance of stainless steel. It also stabilizes the austenite phase, lowering the Ms point and influencing the formation of retained austenite. It also improves hardenability, thereby increasing the mechanical strength of the base material (matrix), ensuring the mechanical strength of the aged material. On the other hand, excessive Co content can result in excessive formation of retained austenite during solution treatment, preventing sufficient hardness from being achieved by aging, and also reducing toughness. It was observed that, in the aged plate materials produced from the steels of Examples 1 to 11, Co was found to be more abundant in the ε-Cu phase and less abundant in the G phase. This indicates that Co influences the precipitation morphology of the ε-Cu phase and the G phase. Taking these factors into consideration, the Co content is set within the range of 0.03 to 0.80%, preferably 0.05 to 0.50%, and more preferably 0.06 to 0.30%, by mass.
[0050] P is an element that inevitably gets mixed into steel. It segregates at grain boundaries and is concentrated in the final solidified portion during casting, promoting solidification cracking and reducing hot workability. Therefore, it is desirable to reduce it as much as possible, but excessive refining increases manufacturing costs. Taking these factors into consideration, the P content is set to 0.04% or less, preferably 0.030% or less, and more preferably 0.025% or less, by mass.
[0051] S is an element that is inevitably mixed into steel. It forms compounds with Mn to become inclusions, reducing corrosion resistance. Furthermore, it segregates at grain boundaries and reduces hot workability. Therefore, it is desirable to reduce S content as much as possible, but excessive refining increases manufacturing costs. Taking these factors into consideration, the S content is set to 0.0020% or less, preferably 0.0015% or less, and more preferably 0.0010% or less, by mass.
[0052] While typical embodiments of the present invention and modifications based thereon have been described above, the present invention is not necessarily limited to these, and a person skilled in the art will be able to find various alternative embodiments and modifications without departing from the spirit of the present invention or the scope of the appended claims.
Claims
1. In mass%, C: 0.01-0.07%, Si: 0.05-2.25%, Mn: 0.5-5.0%, Ni: 4.5-10.0%, Cr: 10.0-17.0%, Mo: 0.1-1.50%, Cu: 0.30-5.0%, Al: 0.001-0.100%, N: 0.001-0.020%, Ti: 0.15-0.55%, Nb: 0.15-0.45%, Co: 0.03-0.80%, P: 0.04% or less, S: 0.0020% or less, and the balance being Fe and unavoidable impurities, The component composition is as follows, where the mass % of element M is [M]: MA=[Ni]+0.65×[Mn]+0.23×[Si]+0.62×[Cr]+0.25×[Mo]+0.35×[Cu]+30.6×([C]+[N])-16.5 The MA defined as is in the range of 1.0 to 4.5, and H=[Cu]+0.6×[Ni]+1.8×[Si]+3.8×[Ti]+1.8×[Nb]-0.9×[Mn]-13.8×([C]+[N]) 2. A precipitation-hardened martensitic stainless steel for press plates, characterized in that H, defined by the formula (1), is in the range of 5.0 or more.
2. In mass%, C: 0.01-0.07%, Si: 0.05-2.25%, Mn: 0.5-5.0%, Ni: 4.5-10.0%, Cr: 10.0-17.0%, Mo: 0.1-1.50%, Cu: 0.30-5.0%, Al: 0.001-0.100%, N: 0.001-0.020%, Ti: 0.15-0.55%, Nb: 0.15-0.45%, Co: 0.03-0.80%, P: 0.04% or less, S: 0.0020% or less, and the balance being Fe and unavoidable impurities, The component composition is as follows, where the mass % of element M is [M]: H=[Cu]+0.6×[Ni]+1,8×[Si]+3.8×[Ti]+1.8×[Nb]-0.9×[Mn]-13.8×([C]+[N]) H defined as above is set to a range of 5.0 or more, A solution-hardened precipitation-hardened martensitic stainless steel for press plates, characterized in that it has a two-phase structure of martensite phase + retained austenite phase, the amount of the retained austenite phase being 0.2 to 8 volume %, and the hardness is less than 380 HV.
3. The component composition is as follows, where the mass % of element M is [M]: MA=[Ni]+0.65×[Mn]+0.23×[Si]+0.62×[Cr]+0.25×[Mo]+0.35×[Cu]+30.6×([C]+[N])-16.5 3. The precipitation hardening martensitic stainless steel solution material for press plates according to claim 2, wherein the MA defined by is in the range of 1.0 to 4.
5.
4. In mass%, C: 0.01-0.07%, Si: 0.05-2.25%, Mn: 0.5-5.0%, Ni: 4.5-10.0%, Cr: 10.0-17.0%, Mo: 0.1-1.50%, Cu: 0.30-5.0%, Al: 0.001-0.100%, N: 0.001-0.020%, Ti: 0.15-0.55%, Nb: 0.15-0.45%, Co: 0.03-0.80%, P: 0.04% or less, S: 0.0020% or less, and the balance being Fe and unavoidable impurities, The component composition is as follows, where the mass % of element M is [M]: MA=[Ni]+0.65×[Mn]+0.23×[Si]+0.62×[Cr]+0.25×[Mo]+0.35×[Cu]+30.6×([C]+[N])-16.5 The MA defined as is in the range of 1.0 to 4.5, Aged precipitation hardened martensitic stainless steel for press plates, characterized by having a hardness of 450 HV or more.
5. The component composition is H=[Cu]+0.6×[Ni]+1.8×Si+3.8×[Ti]+1.8×[Nb]-0.9×[Mn]-13.8×([C]+[N]) 5. The aging-treated precipitation-hardened martensitic stainless steel for press plates according to claim 4, wherein H, as defined by the following formula, is in the range of 5.0 or more.
Citation Information
Patent Citations
High-strength precipitation-hardening stainless steel used for laminated board and manufacturing method thereof
CN111101081A
Precipitation-hardening type martensitic stainless-steel with high strength superior in corrosion resistance
JP2002161343A
Precipitation-hardening martensitic stainless steel
JP2021134395A
Precipitation hardening martensitic stainless steel
WO2012111188A1
Precipitation-hardening type martensitic stainless steel sheet having excellent fatigue resistance
WO2021256145A1